1997
DOI: 10.1039/a607212g
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation of the carbaborane nido-7-NH2But-7-CB10 H12: crystal structures of nido-7-NH2But-7-CB10 H12 and [NEt3(CH2Ph)][ nido-7-NHBut-7-CB10H12 ]

Abstract: The crystal structure of nido-7-NH 2 Bu t -7-CB 10 H 12 1 has been determined by X-ray diffraction. The compound crystallises in the orthorhombic space group Pbca [a = 10.507( 5), b = 13.805(6), c = 18.093(9) Å]. The nidoicosahedral structure was established with two endo-B᎐H᎐B and two NH 2 hydrogen atoms located in Fourierdifference maps and refined. The structure determination is also supported by 11 B-{ 1 H}-11 B-{ 1 H} correlation NMR spectroscopy. A molecular orbital calculation and frontier density analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…This was readily accessed by routes parallel to those that gave 1-3, 8,10, 16 namely treatment in THF of the appropriate carborane trianion with a THF solution of the reagent [ReBr(CO) 3 (THF) 2 ]. 18 Thus, the reaction in THF of the carborane 7-NH 2 Bu t -nido-7-CB 10 H 12 19 with Bu n Li (3 equiv) gives the putative salt Li 3 [7-NHBu t -nido-7-CB 10 H 10 ]. To this was added a THF solution of [ReBr(CO) 3 (THF) 2 ], giving [1-NHBu t -2,2,2-(CO) 3 -closo-2,1-ReCB 10 H 10 ] 2− , which was isolated as the bis-[N(PPh 3 ) 2 ] + salt 4 by addition of [N(PPh 3 ) 2 ]Cl.…”
Section: Resultsmentioning
confidence: 99%
“…This was readily accessed by routes parallel to those that gave 1-3, 8,10, 16 namely treatment in THF of the appropriate carborane trianion with a THF solution of the reagent [ReBr(CO) 3 (THF) 2 ]. 18 Thus, the reaction in THF of the carborane 7-NH 2 Bu t -nido-7-CB 10 H 12 19 with Bu n Li (3 equiv) gives the putative salt Li 3 [7-NHBu t -nido-7-CB 10 H 10 ]. To this was added a THF solution of [ReBr(CO) 3 (THF) 2 ], giving [1-NHBu t -2,2,2-(CO) 3 -closo-2,1-ReCB 10 H 10 ] 2− , which was isolated as the bis-[N(PPh 3 ) 2 ] + salt 4 by addition of [N(PPh 3 ) 2 ]Cl.…”
Section: Resultsmentioning
confidence: 99%
“…The molecules 11 are the first mixed sandwich complexes of rhodium with arenes and a monocarbollide ligand, and are isolobal with many cationic cyclopentadienide complexes [Rh(g 6 -arene)(g 5 -C 5 R 5 )] + . The mode of formation of 11 demonstrates the readiness of the {7-NH 2 Bu t -nido-7-CB 10 H 10 } unit to deprotonate at the exo-polyhedral N atom [24], a feature that will be of greater significance in the compounds of molybdenum, tungsten and rhenium described later.…”
Section: Rhodium Compoundsmentioning
confidence: 97%
“…We anticipated that we might prepare an analogous dianionic monocarbollide species [1-NHBu t -2-(g 3 -C 3 H 5 )-2,2-(CO) 2 -closo-2,1-MoCB 10 H 10 ] 2À by deprotonating 7-NH 2 Bu t -nido-7-CB 10 H 12 [30] with 3 equivalents of LiBu n to generate [7-NHBu t -nido-7-CB 10 It was subsequently found that 15a could be more straightforwardly prepared and in better yield by the interaction of the lithium salt of the monoanionic species [7-NHBu t -nido-7-CB 10 H 12 ] À [24] with [Mo(CO) 6 ] in refluxing NCMe, followed by addition of [N(PPh 3 ) 2 ]Cl [31]. In the synthesis the two face-bridging protons of the carborane are reduced and eliminated as dihydrogen with a concomitant two-electron oxidation of the molybdenum.…”
Section: Molybdenum and Tungsten Compoundsmentioning
confidence: 99%
“…NMR spectra were recorded at the following frequencies: 1 H 360.1, 13 C 90.6, 11 B 115.5 and 31 P 145.8 MHz. The complexes [CuCl(PPh 3 )] 4 , 12 [N(PPh 3 ) 2 ][2,2,2,2-(CO) 4 -closo-2,1-MoCB 10 H 11 ] 2d and 2a, 6 and the carbaboranes 7-NH 3 -nido-7-CB 10 H 12 , 13 7-NMe 3 -nido-7-CB 10 H 12 14 and 7-NH 2 Bu t -nido-7-CB 10 H 12 15 were prepared according to the literature. The [NHMe 3 ] ϩ and [N(PPh 3 ) 2 ] ϩ salts of [nido-7-CB 10 H 13 ] Ϫ were synthesized by methods similar to that of Knoth et al 13 and [FeI(CO) 2 (η-C 5 Me 5 )] was prepared from [Fe(CO) 2 (η-C 5 Me 5 )] 2 .…”
Section: Experimental Generalmentioning
confidence: 99%